Use of a Telehealth System to Enhance a Home Exercise Program for a Person With Parkinson Disease: A Case Report. Issue 1 (January 2018) - Chatto, Charlotte A.; York, Paul T.; Slade, Catherine P.; Hasson, Scott M.
Abstract : Background and Purpose: This case addresses feasibility of a home-based telehealth system to enhance home exercise program (HEP) adherence for a patient with Parkinson disease (PD). We describe START— System for Technology-Augmented Rehabilitation and Training —and discuss outcomes after integrating START into the HEP component of an established therapy protocol, Lee Silverman Voice Technique BIG (LSVT BIG). Case Description: The participant was a 67-year-old woman with PD at Hoehn and Yahr Stage II. Intervention: During the first 4 weeks of a 4-month intervention, a physical therapist guided the participant through the LSVT BIG protocol. START was introduced at week 3; the participant was encouraged to complement her daily HEP through the end of the fourth month with START. Outcomes: Improvements in gait, endurance, balance confidence, and quality of life were observed from the start of the assessment to the end of month 1. By month 4, the participant maintained or improved with respect to these outcomes. Monitored by START, the rate of adherence to her twice-daily HEP prescription was 24%, but her daily participation rate was 78%. The participant's satisfaction with the START system was high, although autonomous feedback provided by START was a limiting concern. There were no technical issues or adverse events reported. Discussion: This case supports START as a feasible HEP telehealth solution for physical therapy, given that increased long-term exercise adherence may improve health outcomes for people with PD. The outcomes of this case study support further investigation into the use of START for people with PD. Video Abstract available for more insights from the authors (see Video; Supplemental Digital Content 1, http://links.lww.com/JNPT/A192 ). Abstract : Supplemental Digital Content is Available in the Text.